2010
DOI: 10.1002/dneu.20829
|View full text |Cite
|
Sign up to set email alerts
|

GAP43 phosphorylation is critical for growth and branching of retinotectal arbors in zebrafish

Abstract: Visual activity acts via NMDA Receptors to refine developing retinotectal maps by shaping retinal arbors. Retinal axons add and delete transient branches, and the dynamic rates increase when MK801 blocks NMDARs, as if this prevents release of a stabilizing signal. Ca(++) entry through NMDARs activates phospholipase A2 (cPLA2) to release arachidonic acid (AA), which taps into a presynaptic growth control mechanism. NCAM, L1, N-cadherin, and FGF all stimulate axon growth via AA activation of protein kinase C to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
40
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(43 citation statements)
references
References 86 publications
3
40
0
Order By: Relevance
“…As illustrated in Pathway B, CaMKII phosphorylation of its target protein GAP-43 functions as an activator of Ga i/o signaling within the cell. CaMKII phosphorylation of GAP-43 has also been shown to promote its dissociation from CaM (Denny, 2006;Leu et al, 2010), a finding consistent with our crosslinking experiments showing an effect of Bgtx on GAP-43/CaM dissociation within the cell (Fig. 2).…”
Section: Gprin1 Scaffolds A7/gpc Signaling During Growthsupporting
confidence: 90%
See 1 more Smart Citation
“…As illustrated in Pathway B, CaMKII phosphorylation of its target protein GAP-43 functions as an activator of Ga i/o signaling within the cell. CaMKII phosphorylation of GAP-43 has also been shown to promote its dissociation from CaM (Denny, 2006;Leu et al, 2010), a finding consistent with our crosslinking experiments showing an effect of Bgtx on GAP-43/CaM dissociation within the cell (Fig. 2).…”
Section: Gprin1 Scaffolds A7/gpc Signaling During Growthsupporting
confidence: 90%
“…The phosphorylation of GAP-43 by protein kinase C (PKC) (Esdar et al, 1999) and CaMKII (Denny, 2006;Leu et al, 2010) or dephosphorylation by calcineurin (PP2B) (Liu and Storm, 1989;Madsen et al, 1998) has been shown to regulate CaM association and neurite growth. In its unphosphorylated form, GAP-43 binds CaM leading to an inhibition in neurite growth (Skene, 1990;Slemmon et al, 1996).…”
Section: Resultsmentioning
confidence: 99%
“…Transfecting a permanently phosphorylated GAP43 into cells increases branching and outgrowth. The axons arborize with several focal areas instead of just one, disrupting the retinotectal map by stabilizing incorrect connections [186]. These known factors interact with many additional molecules, activity and visual experience, and downstream factors to shape the arbors.…”
mentioning
confidence: 99%
“…GAP43 is usually targeted to the end of the axon, where it first causes growth cone collapse and then initiates branching from the growth cone remnants [186]. When overexpressed, GAP43 causes larger RGC arbors through faster growth, increasing the number of branches, the area covered, and total branch length.…”
mentioning
confidence: 99%
See 1 more Smart Citation